2009
DOI: 10.1007/s10695-009-9364-0
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Atlantic cod Gadus morhua head kidney leukocytes to phytase produced by gastrointestinal-derived bacteria

Abstract: This study identified phytase-producing bacteria that were previously isolated from the gastrointestinal tract of Atlantic cod, Gadus morhua and determined its effect on head kidney leukocytes. Out of the 216 bacterial strains tested, the two phytase producers were identified as Pseudomonas sp. and Psychrobacter sp. based on their 16S rDNA sequence. Crude phytase from these two bacterial strains was produced employing the shake flask method. Even though the total protein of the crude phytase was not significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Similarly, the values of RBCs, WBCs and Hb were found higher in Cyprinus carpio fed diets supplemeted at 500 FTU kg -1 level of phytase in soya protein based diet (Sardar et al, 2007). Encouraging results were found when phytase was used in Gadus morhua (Atlantic cod) feed which resulted in higher number of WBCs as compared to fish fed control diet (Lazado et al, 2010). Hemoglobin (Hb) level in fish fed phytase supplemented diet was slightly higher than that of fish fed a diet without phytase, but was not significantly (p<0.05) different from that of other dietary treatments (Yoo and Bai, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, the values of RBCs, WBCs and Hb were found higher in Cyprinus carpio fed diets supplemeted at 500 FTU kg -1 level of phytase in soya protein based diet (Sardar et al, 2007). Encouraging results were found when phytase was used in Gadus morhua (Atlantic cod) feed which resulted in higher number of WBCs as compared to fish fed control diet (Lazado et al, 2010). Hemoglobin (Hb) level in fish fed phytase supplemented diet was slightly higher than that of fish fed a diet without phytase, but was not significantly (p<0.05) different from that of other dietary treatments (Yoo and Bai, 2014).…”
Section: Discussionmentioning
confidence: 90%
“…Previously, we found that two of these bacteria could produce phytase and therefore we attempted to characterize them for further applications. They were identified as belonging to the genera Pseudomonas (GP21) and Psychrobacter (GP12) based on their 16s rDNA sequences [20].…”
Section: Bacterial Origin and Culture Conditionsmentioning
confidence: 99%
“…(Lazado et al . ). These host‐derived bacteria have the capability to modulate immune responses in the head kidney leucocytes of the fish (Lazado et al .…”
Section: Introductionmentioning
confidence: 97%